2018
DOI: 10.1111/jvp.12672
|View full text |Cite
|
Sign up to set email alerts
|

Pharmacokinetics of florfenicol and its metabolite florfenicol amine in crucian carp (Carassius auratus) at three temperatures after one single intramuscular injection

Abstract: The pharmacokinetic profiles of florfenicol (FF) or florfenicol amine (FFA) in crucian carp were compared at different water temperatures after single intramuscular administration of FF at 10 mg/kg bodyweight. The concentrations of FF and FFA were determined by a high-performance liquid chromatography method, and then, the concentration versus time data were subjected to compartmental analysis using a one-compartment open model. At the water temperatures of 10, 20, and 25°C, the peak concentrations (C s) of FF… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
14
1

Year Published

2018
2018
2022
2022

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 29 publications
(17 citation statements)
references
References 25 publications
2
14
1
Order By: Relevance
“…The pharmacokinetics of FFC in tilapia (Oreochromis aurea) at 22 and 28°C showed that the AUC values of the low-temperature group were greater than those of the high-temperature group, which was consistent with the results of our study (Feng & Jia, 2008). The same result has been reported for FFC in crucian carp (Yang et al, 2018 2002). Considering that the sum of the FFC and FFA concentration is more accurate, we calculated two values of WDT.…”
Section: Discussionsupporting
confidence: 88%
“…The pharmacokinetics of FFC in tilapia (Oreochromis aurea) at 22 and 28°C showed that the AUC values of the low-temperature group were greater than those of the high-temperature group, which was consistent with the results of our study (Feng & Jia, 2008). The same result has been reported for FFC in crucian carp (Yang et al, 2018 2002). Considering that the sum of the FFC and FFA concentration is more accurate, we calculated two values of WDT.…”
Section: Discussionsupporting
confidence: 88%
“…It indicates the elimination rate in vivo. In this study, the t 1/2(ke) was 75.13 hr, which was far higher than that in crucian (31.66 hr) (Yang et al., ; Yang et al., ). The MRT of FF in plasma was also long (100.6 hr).…”
Section: Resultscontrasting
confidence: 54%
“…There are many factors affecting the pharmacokinetics and residue elimination times in aquatic animals including species and physiological differences, dosage, route of administration, temperature, salinity, and pH. Among these factors, water temperature is the most influential (Yang et al, ; Yang, Yang, Wang, Kong, & Liu, ). Therefore, the clinical withdrawal period should be determined according to the specific fish species and the actual breeding environment.…”
Section: Discussionmentioning
confidence: 99%